Application of Tahsin and Tahfidz Models to Delinquent Students - Ati Kusmawati; Nelly Marhayati (UM Purwokerto Press, 2023)
Student delinquency has become a worrying phenomenon. Till now, there has been no study that has looked at students' delinquency from the Psycho-Spiritual Healing approach using the Koran perspective with the tahsin and tahfidz models. This paper aimed to complement the shortcomings of previous studies that ignore the contribution of the Koran in solving students' delinquency problems. The application of the tahsin and tahfidz models was carried out in three stages. The first was to get students accustomed to reading and memorizing Koran. The second was disciplining students, and the third was evaluating student achievement.